1983
DOI: 10.1002/j.1875-9114.1983.tb03231.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Beta‐Adrenergic Blocking Agents in Anxiety Disorders and Schizophrenia

Abstract: In the 1960s, several studies reported that propranolol and other beta‐blocking drugs appeared especially useful in patients with physical symptoms of anxiety. However, subsequent reports produced conflicting findings, and at this time the efficacy of propranolol in anxiety disorders is not clearly established. Propranolol's utility in anxiety states may be entirely restricted to those anxiety patients whose physical symptoms have not adequately responded to benzodiazepine therapy. This places the beta‐blocker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…This high-dose requirement suggests that β-blockers are acting centrally rather than peripherally (see Neppe 1989). Such high doses have been reported to cause serious side effects, including delirium, gastrointestinal symptoms, and paradoxical acute hypertension (Hayes and Schulz 1983). The improvements reported with propranolol generally have been in negative symptoms such as poor socialization, emotional withdrawal, and anergia, as well as on agitation, assaultiveness, and irritability, rather than on hallucinations or delusions.…”
Section: Psychosesmentioning
confidence: 99%
See 1 more Smart Citation
“…This high-dose requirement suggests that β-blockers are acting centrally rather than peripherally (see Neppe 1989). Such high doses have been reported to cause serious side effects, including delirium, gastrointestinal symptoms, and paradoxical acute hypertension (Hayes and Schulz 1983). The improvements reported with propranolol generally have been in negative symptoms such as poor socialization, emotional withdrawal, and anergia, as well as on agitation, assaultiveness, and irritability, rather than on hallucinations or delusions.…”
Section: Psychosesmentioning
confidence: 99%
“…The doses needed for central β 1 blockade appear considerably higher than required for peripheral β-blockade (e.g., Hayes and Schulz 1983).…”
Section: Introductionmentioning
confidence: 99%
“…of beta-adrenoceptor antag onists have been suggested in therapeutic areas such as psychiatry and neurology (1). However, the mechanism of action of beta antagonists on the central nervous system is still unclear.…”
Section: Applicationsmentioning
confidence: 99%
“…Another group of drugs having certain importance in treatment of patients with schizophrenia is cardiovascular agents. In the 1970s and early 1980s beta-adrenergic blocking drugs, such as propranolol, used in high doses, were supposed to be effective as alternative antipsychotics in neuroleptic resistant patients ( Hayes and Schulz, 1983 ). It has also been suggested that beta-adrenergic antagonists are effective in the treatment of acute akathisia ( Lipinski et al , 1988 ; Kornischka et al , 2007 ) and aggression associated with schizophrenia ( Haspel, 1995 ).…”
Section: Introductionmentioning
confidence: 99%